Local wisdom of manongkah kerang as biology learning context in independent curriculum: A narrative review - Hasni Hasni; Siti Sriyati (JPBIO (Jurnal Pendidikan Biologi), 2026)
Local wisdom holds significant potential as a contextual biology learning resource, yet its integration into the Independent Curriculum remains underexplored, particularly in coastal communities. This study aims to examine the integration of the local wisdom of the Duano Tribe's mussel tradition into biology learning in the Independent Curriculum. This tradition contains ecological knowledge, organismal adaptation, biomechanics of motion, as well as conservation values relevant to biological concepts. The research uses the Narrative Literature Review (NLR) design by examining articles published in 2018–2025 that discuss local wisdom, ethnopedagogy, coastal biology, and curriculum implementation. The analysis is carried out through thematic coding to identify concept patterns and potential integration in learning. The results of the study show that the tradition of mussels can be used to strengthen the understanding of coastal ecosystems, the morphological and physiological adaptation of blood mussels, as well as the issue of environmental change. The integration of local potential is also relevant for the development of inquiry-based learning activities and project-based learning, as well as supporting the achievement of the Pancasila Student Profile. Overall, this study confirms that the manongkah kerang tradition has strong educational value and can be implemented as a contextual learning resource to improve students' ecological competence, cultural identity, and environmental awareness.